Extremist Radicalism and Terrorist Inroads in West Africa: Understanding the Threat - Solomon Kofi Amoah; Anthony Ayim; Danladi Abah; Kobina Abaka Ansah (Centre for Behaviour and Wellness Advocacy, 2017)
While research has not yet established the regional consequences of terrorism, its immediate effects on states that have been hit (i.e. Mali, Niger, Burkina Faso and Nigeria), and the spill over effects in neighbouring countries cannot be discounted. This paper analyses the challenge of violent extremism in Africa based on existing evidence from across the West African sub- region. It pays particular attention to the recruitment of young people in Africa into extremist causes on the continent and beyond and proffers measures for their curtailment. The paper argues that terrorism in contemporary Africa undermines democratization, good governance, peace and security and regional development. It also recommends three-pronged strategies for addressing the miasma of extremist radicalism and its associated violence in West Africa, namely, governance, development and security reforms. While it may be difficult to absolutely curtail the activities of terrorist organizations in West Africa. Countries with minimal vulnerabilities like Ghana, Sierra Leone, Liberia and others should intensify efforts towards increased border and cyber security surveillance, sustained de-radicalization programmes and youth empowerment programmes to curb unemployment in earnest.